Sickle Cell Anemia: Medicines of choice for treatment in Brazil - Lopes, Josyany Melo; Barbosa, Ana Patrícia Matos; Branco, Alessandra Camillo da Silveira Castelo (Seven Editora, 2023)
Sickle cell anemia is a hematological disease with prevalence in Africa, the Middle East, India, and Central America. It happens when there is a defect in the red blood cell, due to the abnormal presence of a hemoglobin S. This condition is caused by a genetic mutation that affects the structure of hemoglobin, the protein responsible for transporting oxygen in red blood cells. The present study aimed to analyze the drugs currently used in Brazil for sickle cell anemia with the hypothesis that there are new therapeutic alternatives under development. Searches were carried out in databases such as Science direct, Pubmed, Scielo and 52 articles involving the theme of sickle cell anemia were found, and after applying the inclusion criteria, 10 articles remained for complete reading, where 4 were used in this integrative review. The new studies include the substances crizanlizumab, hydroxyurea and selexipag as a projection for medicines. Among these, crizanlizumab and selexipag were effective in reducing the frequency and severity of vaso-occlusive crises, as well as in improving the quality of life of patients, and only hydroxyurea did not show effective results due to low treatment adherence. Therefore, there are new drugs in research phases and also blood transfusion therapy, bone marrow transplantation, and new pharmacological approaches are being developed for the treatment of sickle cell anemia. DOI:https://doi.org/10.56238/sevened2023.004-053